2017
DOI: 10.1111/ffe.12726
|View full text |Cite
|
Sign up to set email alerts
|

The influence of partial surface shot peening on fatigue crack growth behaviour of a high‐strength ferritic steel

Abstract: The effects of partial surface shot peening on the fatigue crack growth behaviour of a ferritic steel have been experimentally investigated in this paper. Dog‐bone specimens fabricated from Optim700QL were tested under tension‐tension fatigue loads. Three distinct extents of partial shot peening, with respect to the crack tip and specimen symmetry line, were tested. The fatigue crack growth results from these experiments have been compared with those obtained from the same specimen geometry but with no peening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In this work, the material utilised for examination was the high-strength ferritic steel referred to as 700 Optim QL [14]. In the completion of this work, 4-point bend specimens underwent machining from an 700 Optim QL plate.…”
Section: Materials and Specimen Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the material utilised for examination was the high-strength ferritic steel referred to as 700 Optim QL [14]. In the completion of this work, 4-point bend specimens underwent machining from an 700 Optim QL plate.…”
Section: Materials and Specimen Designmentioning
confidence: 99%
“…In this work, the material utilised for examination was the high-strength ferritic steel referred to as Optim700QL. 14 In the completion of this work, four-point bend specimens underwent machining from an Optim700QL plate. As can be seen detailed in Figure 3, the dimensions of the four-point bend specimens were as follows: 330 mm length, 100 mm width, and 25 mm thickness.…”
Section: Materials and Specimen Designmentioning
confidence: 99%
“…Mechanical behavior of composites under fatigue loading seems to be affected by fiber breakage, matrix cracking, interfiber fracture, and delamination between the layers. Different types of polymers such as epoxy, polyester, and vinylesters were used as a base for the composite materials [1] [2]. Many studies have confirmed that the incorporation of the small volume fraction of nanofibers as a filler in the polymer led to improve several fatigue properties.…”
Section: Introductionmentioning
confidence: 99%